Neonatal ovarian cysts: therapeutic dilemma. Issue 7 (July 1988) - Widdowson, D J; Pilling, D W; Cook, R C
Abstract : Seven cases of neonatal ovarian cysts that presented over the past seven years were studied. Complications included torsion and rupture and usually occurred in cysts more than 5 cm in diameter. Surgical removal, either oophorectomy or cystectomy, was the treatment of choice. Because even cystectomy results in loss of normal ovarian tissue, and because spontaneous regression of cysts less than 5 cm in diameter can occur, a more conservative approach is now proposed. Regular ultrasonography alone is recommended if the cysts are less than 5 cm in diameter, and aspiration of the cysts followed by regular ultrasonographs if the cysts are more than 5 cm in diameter. Operation should be reserved for recurrent cysts or for those with complications. Cysts diagnosed antenatally may be aspirated in utero if there are signs of thoracic compression.